UAP56 couples piRNA clusters to the perinuclear transposon silencing machinery. - Zhang, F; Wang, J; Xu, J; Zhang, Z; Koppetsch, B; Schultz, N; Vreven, T; Meignin, C; Davis, I; Zamore, P; Weng, Z; Theurkauf, W (2012)
piRNAs silence transposons during germline development. In Drosophila, transcripts from heterochromatic clusters are processed into primary piRNAs in the perinuclear nuage. The nuclear DEAD box protein UAP56 has been previously implicated in mRNA splicing and export, whereas the DEAD box protein Vasa has an established role in piRNA production and localizes to nuage with the piRNA binding PIWI proteins Ago3 and Aub. We show that UAP56 colocalizes with the cluster-associated HP1 variant Rhino, that nuage granules containing Vasa localize directly across the nuclear envelope from cluster foci containing UAP56 and Rhino, and that cluster transcripts immunoprecipitate with both Vasa and UAP56. Significantly, a charge-substitution mutation that alters a conserved surface residue in UAP56 disrupts colocalization with Rhino, germline piRNA production, transposon silencing, and perinuclear localization of Vasa. We therefore propose that UAP56 and Vasa function in a piRNA-processing compartment that spans the nuclear envelope.